Nanocellulose-silicon-based hybrid material, preparation and application thereof, and thermoplastic polymer composite material

By wrapping silicone on cellulose and nanosilica and hydrolyzing with silane coupling agent, cellulose-silicon-based hybrid materials were prepared, which solved the problem of poor dispersion of nanocellulose and improved the mechanical and thermal properties of the polymer matrix.

CN119639022APending Publication Date: 2025-03-18QUZHOU RES INST OF ZHEJIANG UNIV

Patent Information

Application Number
CN202510163603.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Nanocellulose has problems such as poor dispersion in practical applications, which limits its application in the field of high-performance composite materials.

Method used

By encapsulating silicone on cellulose and nanosilica and combining with the hydrolysis reaction of silane coupling agent, a cellulose-silicon-based hybrid material is prepared to achieve uniform dispersion and efficient synergistic enhancement of nanocellulose and nanosilica.

Benefits of technology

It improves the mechanical properties and thermal properties of the polymer matrix, enhances the stability and dispersion of the material, and has an environmentally friendly process, simple and easy to be produced in industrial form.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119639022A_ABST
    Figure CN119639022A_ABST
Patent Text Reader

Abstract

The invention relates to a nanocellulose-silicon-based hybrid material, preparation and application thereof and a thermoplastic polymer composite material. Comprising the following steps: combining nano SiO2 containing hydrophilic hydroxyl on the surface with hydroxyl on the surface of cellulose, then adding a silane coupling agent, reacting and hydrolyzing the silane coupling agent to obtain silanol, combining the silanol with hydroxyl on the surface of nano SiO2 particles and hydroxyl on the surface of nano cellulose, drying, dehydrating the silanol into siloxane, and grafting the siloxane on the surface of nano cellulose / SiO2, thereby obtaining the nano SiO2 / silanol composite material. Grinding to obtain a nanocellulose-silicon-based hybrid material, blending the obtained hybrid material with a thermoplastic polymer matrix, and preparing a corresponding product through a thermal forming process. The process is environment-friendly, the method is simple, the product is easy to form, operation and control are simple and convenient, and industrial production is facilitated; the prepared hybrid material has good stability, dispersibility and polymer matrix compatibility, and shows excellent mechanical properties and thermal properties when applied to thermoplastic polymers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of plant fiber reinforced polymer composite materials, and specifically relates to a nano cellulose-silicon based hybrid material and its preparation and application and a thermoplastic polymer composite material. Background Art

[0002] Nanocellulose, as a natural polymer material with excellent mechanical properties, renewability and biodegradability, has attracted widespread attention from researchers. Nanocellulose has high specific surface area, high strength and unique nano-size effect, which makes it have broad application prospects in many fields. However, nanocellulose has certain limitations in practical applications, such as poor dispersibility, which limits its application in the field of high-performance composite materials.

[0003] Studies have shown that green and efficient pretreatment methods can be used to achieve directional exfoliation and surface modification of nanocellulose, thereby improving its dispersibility and compatibility in polymer matrices. Then, functional nanoparticles such as carbon nanotubes and graphene are hybridized with nanocellulose using in-situ polymerization or physical adsorption methods to prepare nanocellulose hybrid materials with excellent performance.

[0004] In previous studies: CN 111848916 A discloses a silanized nanocellulose modified waterborne polyurethane and a preparation method thereof, wherein castor oil (terminal-OH component) and isophorone diisocyanate (terminal-NCO component) are used as two main raw materials to synthesize a modified waterborne polyurethane (WPU) according to a certain functional group ratio (NCO / OH) through an in-situ polymerization reaction, and octaaminopropyl silsesquioxane nanocellulose is added during the synthesis process to enhance performance. CN 116874619 A uses trimethylsilane and stannous octoate as modified materials to treat nanocrystalline cellulose, wherein trimethylsilane and stannous octoate react with the solution to automatically carry out acid-base synthesis, reduce the acidity in the deionized water wastewater generated by the material washing after the reaction, and make the material non-polar through anodic treatment, thereby enhancing the hydrophobicity of the hydrophobic modified material of the modified nanocrystalline cellulose. However, the above modification method requires the control of multiple reaction conditions, takes a long time, and involves some special chemicals and solvents, has high requirements for equipment, and is difficult to produce in practice.

[0005] The advantage of the present invention is that compared with the strategy of hydrophobic modification of nanocellulose surface (which often uses a large amount of organic solvents, has a low grafting rate due to steric hindrance effect, and unstable physical adsorption), this method does not require a large amount of organic solvents, has a controllable grafting rate, has a stable silica loading, and is easy to evenly disperse nanocellulose and nanosilica, achieving multiple goals at one stroke and realizing the synergistic enhancement effect of fiber reinforcement and particle reinforcement. Summary of the invention

[0006] Based on the above problems, the object of the present invention is to provide a method for preparing a nanocellulose hybrid material and its application in thermoplastic polymers to improve the mechanical properties and thermal properties of thermoplastic polymers.

[0007] In one aspect, the present invention provides a cellulose-silicon based hybrid material, characterized in that the hybrid material components include: cellulose, silicon dioxide and siloxane wrapped on cellulose / SiO2; The nanocellulose is one or more of wood cellulose, nanocellulose and cellulose nanocrystals; The silicon dioxide is a hydrophilic nano-silicon dioxide with hydroxyl groups on the surface; the main methods for preparing nano-silicon dioxide include physical method and chemical method. The physical method mainly includes mechanical crushing method; the chemical method includes sol-gel method, hydrolysis precipitation method and gas phase method.

[0008] The siloxane is formed by hydrolysis of a silane coupling agent to form silanol, and the silanol is dried to form siloxane.

[0009] Furthermore, the nano-SiO2 with hydrophilic hydroxyl groups on the surface is combined with the hydroxyl groups on the surface of cellulose, and then a silane coupling agent is added. Under heating and stirring, the silane coupling agent is hydrolyzed to obtain silanol, and the silanol is combined with the hydroxyl groups on the surface of the nano-SiO2. After drying, the silanol is converted into siloxane and wrapped on the surface of cellulose / SiO2, and then the cellulose-silicon-based hybrid material is obtained by grinding. The following steps are included (1) Dispersing cellulose in ultrapure water by stirring; (2) Add nano-silicon dioxide to the dispersed cellulose aqueous solution and stir to make the cellulose evenly dispersed; (3) Add silane coupling agent, heat and stir to hydrolyze the silane coupling agent into silanol and wrap it on cellulose / SiO2; (4) Drying the reaction solution to remove moisture, and grinding to obtain cellulose-silicon-based hybrid material powder.

[0010] Preferably, the nanocellulose fibers are selected from one or more of nanocellulose (diameter 2-10 nm, length 1-5 μm), cellulose nanocrystals (most of the amorphous regions of nanocellulose are removed, and the crystalline regions are retained, with a diameter of 2-6 nm and a length of 100-500 nm), and lignin-containing nanocellulose (containing 2-25% lignin and 2-20% hemicellulose, by mass); Preferably, the silane coupling agent includes but is not limited to one or more of hexadecyltrimethoxysilane, methyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane (KH570), 3-aminopropyltriethoxysilane (KH550), diaminopropyltriethoxysilane (KH560), vinyltriethoxysilane, vinyltrimethoxysilane, etc.; Preferably, the mass of each component is calculated based on the mass of cellulose, the amount of silicon dioxide added is 1-6 times (preferably 2-5 times) the mass of cellulose, and the amount of silane coupling agent added is 0.2-8 times (preferably 1-5 times) the molar mass of cellulose; Preferably, the reaction temperature of the silane coupling agent is 20-90° C. (preferably 40-80° C.), and the stirring rate is 200-1500 rpm (preferably 500-1200 rpm).

[0011] Reaction time 10-60 min (preferably 20-50 min).

[0012] Preferably, the drying method includes one or more of spray drying, oven drying, freeze drying, vacuum drying, etc.

[0013] The hydrophobic properties of the samples were further characterized by water contact angle. The water contact angle of the hybrid material was measured by using a contact angle tester DataPhysicsOCA-20 at room temperature using 3 μL of deionized water. The larger the water contact angle, the more hydrophobic the prepared material is.

[0014] On the other hand, due to the insufficient mechanical and thermal properties of the polymer, the present invention adds cellulose-silicon-based hybrid materials as fillers into the polymer matrix, and the nano-silicon dioxide uses cellulose as a carrier, and the dispersibility in the polymer is improved; Siloxane wraps cellulose / SiO2, shielding the hydrophilic hydroxyl groups on the surface of nano-silicon dioxide and cellulose, so that the hydrophobicity of the hybrid material is improved, thereby improving compatibility with the polymer matrix. Specifically, the following steps are included: (1) adding the ground cellulose-silicon-based hybrid material powder into a polymer matrix in a certain proportion and mixing them evenly by stirring; (2) The mixed material is processed into dumbbell-shaped strips through a thermoforming process.

[0015] Preferably, the nanocellulose-silicon-based hybrid material is 0.2-10% (preferably 1-8%) of the mass of the polymer matrix; Preferably, the polymer matrix includes: one or two of PBAT, PLA, PBS, PP, PE, etc.; Preferably, the thermoforming process includes: hot pressing molding, twin-screw extrusion and injection molding, or one or two thereof.

[0016] The modified polymer matrix is ​​further subjected to mechanical property testing, and the tensile strength and elongation at break are measured by a universal mechanical testing machine, referring to the standard GB / T 16491-2008. The specific steps include: (1) Install the tensile spline on the tensile fixture, select a suitable force sensor, and set the width, thickness, and original gauge length of the tensile part of the spline.

[0017] (2) Set an appropriate stretching rate for the stretching test.

[0018] Compared with the prior art, the gain effect of the present invention is mainly reflected in: By using cellulose as the raw material and introducing inorganic silica particles to be grafted onto cellulose, the dispersibility of the silica particles in the polymer matrix is ​​improved, which is a synergistic enhancement of both the fibers and the particles. At the same time, the silanol and SiO2 obtained by the hydrolysis of the silane coupling agent react with the hydroxyl groups on the surface of the cellulose. The siloxane formed during the drying process can effectively shield the hydroxyl groups on SiO2 and cellulose, thereby improving the hydrophobicity of the hybrid material, improving the compatibility with the polymer, and improving the mechanical properties of the polymer.

[0019] The process of the invention is environmentally friendly, the method is simple, the product is easy to form, the operation and control are simple, and it is conducive to industrial production; the prepared hybrid material has good stability, dispersibility and polymer matrix compatibility, and shows excellent mechanical properties and thermal properties when applied to thermoplastic polymers. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 : Tensile strength and elongation at break of the composite material of Example 1.

[0021] Figure 2 : Tensile strength and elongation at break of the composite material of Example 3.

[0022] Figure 3 : Comparative Example 5 Effect of pure cellulose on the tensile strength and elongation at break of PBAT.

[0023] Figure 4 : Comparative Example 6 Effect of pure nano-SiO2 on the tensile strength and elongation at break of PBAT.

[0024] Figure 5 : Example 1 SEM images of SiO2 loaded on the surface of cellulose, where (a) is the SEM image of the cellulose-silicon-based material at 2k magnification; (b) is the SEM image of the cellulose-silicon-based material at 60k magnification. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail with reference to the following embodiments.

[0026] Water contact angle test: The water contact angle of the hybrid material was measured using deionized water at room temperature using a contact angle tester DataPhysics OCA-20. The larger the water contact angle, the more hydrophobic the prepared material is.

[0027] Tensile performance test: The tensile strength and elongation at break of the composite material were tested by a universal mechanical testing machine. Each group was tested 7 times and the average value was taken. The tensile rate could be 30-50mm / min (40mm / min in this case) depending on the substrate, and the original gauge length was 25mm.

[0028] (1) Install the dumbbell-shaped tensile spline on the fixture, select a 10KN force sensor, and set the width of the tensile part in the middle of the spline to 2mm, thickness to 4mm, and original gauge length to 25mm.

[0029] (2) Perform a tensile test at a tensile rate of 30-50 mm / min (40 mm / min in this case).

[0030] Surface morphology test: The surface morphology characteristics of the cellulose-silicon based hybrid material were observed by scanning electron microscopy at magnifications of 2000 and 60000 times.

[0031] The silane coupling agent was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Example 1

[0032] Preparation of cellulose-silicon based hybrid materials: taking nanocellulose (diameter 2-10 nm, length 1-5 μm), fumed nanosilica (particle size 1-10 nm), and 3-aminopropyltriethoxysilane (KH550) (Shanghai Aladdin Biochemical Technology Co., Ltd.) as examples; Add 5g of nano-silicon dioxide to 100ml of ultrapure water, stir for 15min to make it dispersed evenly, then add 1g of nano-cellulose to the silica aqueous solution, stir for 15min to make it dispersed evenly, and finally add 1.36g of silane coupling agent to the solution, react at 60℃ for 30min, and stir at 1000rpm. After the reaction is completed, the solution is cooled to room temperature and then pre-frozen at -20℃ for 2-4h (3h in this case) to ensure complete freezing, and then freeze-dried for 24h (-55℃). After freeze-drying, the cellulose-silicon hybrid material will partially agglomerate, and it needs to be ground for 10min to obtain the hybrid material powder (particle size is 30-70nm).

[0033] Preparation of PBAT composite materials: Take the polymer matrix PBAT (polybutylene adipate / terephthalate) and the filler addition amount of 1% as an example: 0.4 g of cellulose-silicon-based hybrid material and 39.6 g of PBAT were blended and stirred for 15 min to make them uniformly mixed, melt-blended by a twin-screw extruder, and extruded by the extruder and injection molded into dumbbell-shaped specimens by an injection molding machine.

[0034] The screw speed of the twin-screw extruder (SJZS-10B micro twin-screw extruder) is 50 rpm, and the temperatures of the first to fourth zones (feeding zone, compression zone, melting zone, homogenization zone) are (110°C in the first zone, 130°C in the second zone, 150°C in the third zone, and 170°C in the fourth zone); The injection molding machine (SZS-20 micro injection molding machine) had an injection pressure of 0.3 MPa, a mold temperature of 60°C, and a barrel temperature of 175°C.

[0035] The test results are shown in Table 1 and Figure 1 shown.

[0036] Example 2

[0037] Preparation of cellulose-silicon hybrid materials: Taking wood nanocellulose (containing 2-25% lignin and 2-20% hemicellulose by mass; diameter 2-10 nm, length 1-5 μm), fumed nanosilica (particle size 1-10 nm), and hexadecyltrimethoxysilane (Shanghai Aladdin Biochemical Technology Co., Ltd.) as examples.

[0038] Add 5g of nano-silica to 100ml of ultrapure water, stir for 15min to make it dispersed evenly, then add 1g of nano-cellulose to the silica aqueous solution, stir for 15min to make it dispersed evenly, and finally add 2.14g of silane coupling agent to the solution, react at 60℃ for 30min, and stir at 1000rpm. After the reaction is completed, the solution is cooled to room temperature and then pre-frozen at -20℃ for 2-4h (3h in this case) to ensure complete freezing, and then freeze-dried for 24h (-55℃). The freeze-dried cellulose-silicon-based hybrid material is ground for 10min to obtain a hybrid material powder (particle size of 30-70nm).

[0039] Preparation of PBAT composite materials: Take the polymer matrix PBAT and the addition amount of filler as 1% as an example.

[0040] 0.4 g of cellulose-silicon-based hybrid material and 39.6 g of PBAT were blended and stirred for 15 min to make them uniformly mixed, melt-blended by a twin-screw extruder, and extruded by the extruder and injection molded into dumbbell-shaped specimens by an injection molding machine.

[0041] The screw speed of the twin-screw extruder (SJZS-10B micro twin-screw extruder) is 50 rpm, and the temperatures of the first zone to the fourth zone (feeding zone, compression zone, melting zone, homogenization zone) are (110°C in the first zone, 130°C in the second zone, 150°C in the third zone, and 170°C in the fourth zone); The injection molding machine (SZS-20 micro injection molding machine) had an injection pressure of 0.3 MPa, a mold temperature of 60°C, and a barrel temperature of 175°C.

[0042] The test results are shown in Table 1.

[0043] From the data in Table 1, it can be seen that the water contact angle of cellulose-silicon hybrid material becomes larger and the hydrophobicity becomes better when hexadecyltrimethoxysilane is used as the silane coupling agent. The possible reason is that the alkyl chain (C16) of hexadecyltrimethoxysilane is much longer than the propyl chain (C3) of KH550. It is generally believed that the longer the alkyl chain, the better the hydrophobicity.

[0044] Example 3

[0045] Take nanocellulose (diameter 2-10 nm, length 1-5 μm), sodium silicate acid precipitation SiO2, 3-aminopropyltriethoxysilane (KH550) (Shanghai Aladdin Biochemical Technology Co., Ltd.) as an example Dissolve 10.16g sodium silicate in water to prepare a solution with a mass concentration of 10-20% (here 15%); then soak 1g cellulose in the sodium silicate solution for 6h, keep the temperature at room temperature 26℃, and ensure that the cellulose is fully in contact with the sodium silicate; adjust the pH value of the cellulose sodium silicate solution to 3 by titration with 36% hydrochloric acid and keep the reaction for 3h, and stir appropriately to promote uniform reaction; wash the resulting solution 5-8 times (7 times in this case) to remove unreacted sodium silicate and hydrochloric acid, add 2.14g silane coupling agent to the washed solution, react at 60℃ for 30min, and stir at 1000rpm. After the reaction is completed, the solution is cooled to room temperature and then pre-frozen at -20℃ for 2-4h (here 3h) to ensure complete freezing, and then freeze-dried for 24h (-55℃), and the freeze-dried cellulose-silicon hybrid material is ground for 10min to obtain a hybrid material powder (particle size 30-70nm). The subsequent composite material preparation method (process and conditions) is the same as that in Example 1.

[0046] The test results are shown in Table 1 and Figure 2 shown.

[0047] From the data in Table 1, it can be concluded that the loading amount of nano-silica obtained by in-situ acid precipitation is higher than that obtained by directly adding nano-silica. The possible reason is that chemical bonds or strong interactions are formed between nano-silica and cellulose, which enhances the binding force between the two. Compared with directly mixing or physically connecting silica, this can make silica more firmly loaded on cellulose, thereby improving the stability of the composite material and reducing the shedding or migration of nano-silica.

[0048] Example 4

[0049] Take cellulose nanocrystals (removing most of the amorphous areas of nanocellulose and retaining the crystalline areas, with a diameter of 2-6nm and a length of 100-500nm), gas-phase nano-SiO2 (particle size of 1-10nm), and 3-aminopropyltriethoxysilane (KH550) (Shanghai Aladdin Biochemical Technology Co., Ltd.) as examples. 5g of fumed nano-silica was added to 100ml of ultrapure water and stirred for 15min to make it dispersed evenly. Then 1g of nano-cellulose was added to the silica aqueous solution and stirred for 15min to make it dispersed evenly. Finally, 2.14g of silane coupling agent was added to the solution and reacted at 60℃ for 30min with a stirring speed of 1000rpm. The reaction solution was cooled to room temperature and then pre-frozen at -20℃ for 2-4h (3h in this case) to ensure complete freezing, and then freeze-dried for 24h (-55℃). The freeze-dried cellulose-silicon hybrid material was ground for 10min to obtain a hybrid material powder.

[0050] The subsequent composite material preparation method (process and conditions) is the same as that of Example 1. The test results are shown in Table 1.

[0051] Comparative Example 1 Example 1 was repeated (process and conditions were the same as Example 1), except that the amount of silicon dioxide added was changed to 8 g, and the rest remained unchanged.

[0052] The test results are shown in Table 2.

[0053] By comparing Example 1, it can be seen that the loading amount of silica increased by 5%, but the tensile strength and elongation at break decreased by 2%, and the elongation at break decreased by 7.7%. This may be due to the excessive silica particles agglomerating in the polymer matrix and incomplete siloxane wrapping, which resulted in partial exposure of hydroxyl groups and reduced compatibility between the hybrid material and the polymer matrix.

[0054] Comparative Example 2 Example 1 was repeated (process and conditions were the same as Example 1), except that the molar ratio of the silane coupling agent to the cellulose was changed to 10:1, that is, 13.6 g of KH550 was added, and the rest remained unchanged.

[0055] The test results are shown in Table 2.

[0056] By comparing Example 1, it can be seen that adding too much silane coupling agent improves the hydrophobicity to a certain extent, but the strength of the composite material decreases. The possible reason is that the silane coupling agent over-covers the surface of the nano-silica to form a multi-layer structure, which in turn affects the dispersibility of the nano-silica.

[0057] Comparative Example 3 Example 1 was repeated (the process and conditions were the same as those of Example 1), except that the amount of cellulose-silicon-based hybrid material added to the composite material was changed to 15%, that is, 6 g of the hybrid material was added to 34 g of the PBAT matrix, and the remaining steps were the same.

[0058] The test results are shown in Table 2.

[0059] By comparing the test results, when the addition amount of cellulose-silicon-based hybrid material reaches 15%, the tensile strength decreases by 13.5% and the elongation at break decreases by 14.6%. The possible reason is that too much cellulose-silicon-based hybrid filler is added and agglomerates in the polymer matrix.

[0060] Comparative Example 4 Example 1 was repeated (the process and conditions were the same as Example 1), except that the composite material matrix was changed to PP (polypropylene), and the remaining steps were the same.

[0061] The test results are shown in Table 2.

[0062] By changing the polymer matrix, the reinforcing effect of cellulose-silicon-based hybrid fillers is still obvious. Compared with pure PP (tensile strength 41MPa, elongation at break 607%), the tensile strength is increased by 12.5% ​​and the elongation at break is increased by 18.7%.

[0063] Comparative Example 5 Pure nanocellulose (diameter 2-10 nm, length 1-5 μm) was added to PBAT as a filler, with a mass addition amount of 1%. The specific operation steps were the same as those in Example 1 for the preparation of the composite material (the process and conditions were the same as those in Example 1).

[0064] The test results are shown in Table 2 and Figure 3 shown.

[0065] By comparing Example 1, it can be seen that the tensile strength of the composite material with the simple addition of cellulose decreases by 6%. The possible reason is that the hydrophilic hydroxyl groups on the surface of cellulose lead to its poor compatibility with the polymer matrix, and cellulose is easy to agglomerate in the polymer matrix.

[0066] Comparative Example 6 Pure nano-silicon dioxide (particle size of 1-10 nm) was added to PBAT as a filler, with a mass addition amount of 1%. The specific operating steps were the same as those in Example 1 for the preparation of the composite material (the process and conditions were the same as those in Example 1).

[0067] The test results are shown in Table 2 and Figure 4 shown.

[0068] As an inorganic filler, silicon dioxide itself has a reinforcing effect on the polymer matrix. Compared with Example 1, it is found that the enhancement of polymer performance by cellulose-silicon-based hybrid filler is much higher than that of single silicon dioxide inorganic particles. The possible reason is that in the hybrid filler component, the siloxane formed by the silane coupling agent improves the compatibility of the hybrid filler and the polymer matrix, and the hybrid material includes two components, fiber and particle, which are synergistically reinforced.

[0069] Table 1: Test results of water contact angle, tensile strength, elongation at break and silica loading of Examples 1-3 Performance Indicators Example 1 Example 2 Example 3 Example 4 Water contact angle (°) 122 135 120 121 Tensile strength(MPa) 25.2 26.5 25.5 24.9 Elongation at break (%) 1103 1152 1117 1105 Table 2: Test results of water contact angle, tensile strength, elongation at break and silica loading of comparative examples 1-6 Performance Indicators Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Water contact angle (°) 119 127 120 119 - - Tensile strength(MPa) 22.1 22.05 19.47 45 21.2 23.2 Elongation at break (%) 950 1007 844.5 720.63 1032 1066.7

Claims

1. A nanocellulose-silicon-based hybrid material, characterized in that: The hybrid material components are cellulose, silicon dioxide supported on cellulose and siloxane wrapped on cellulose; The cellulose is one or more of lignin-containing nanocellulose, nanocellulose, and cellulose nanocrystals; The silicon dioxide is a hydrophilic nano-silicon dioxide with hydroxyl groups on the surface and a particle size of 1-10 nm; The siloxane is formed into silanol by hydrolysis of a silane coupling agent, and the silanol combines with hydroxyl groups on the surface of nano-SiO2 and the surface of nano-cellulose. After drying, the silanol is partially dehydrated to become siloxane wrapped on the surface of nano-cellulose and / or SiO2.

2. The nanocellulose-silicon-based hybrid material according to claim 1, characterized in that: The cellulose fibers are selected from nanocellulose, which has a diameter of 2-10 nm and a length of 1-5 μm; cellulose nanocrystals, which are obtained by removing most of the amorphous regions of nanocellulose and retaining the crystalline regions, with a diameter of 2-6 nm and a length of 100-500 nm; lignin-containing nanocellulose, which contains 2-25% lignin and 2-20% hemicellulose by mass; one or more of the following: a diameter of 2-10 nm and a length of 1-5 μm; The silane coupling agent is one or more of hexadecyltrimethoxysilane, methyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, 3-aminopropyltriethoxysilane, diaminopropyltriethoxysilane, vinyltriethoxysilane and vinyltrimethoxysilane.

3. The nanocellulose-silicon-based hybrid material according to claim 1, characterized in that: The main methods for preparing nano-silicon dioxide include physical or chemical methods; The physical method mainly includes mechanical pulverization, which can efficiently grade and separate particles of different particle sizes through ultra-fine pulverization mechanical energy; The chemical method includes one or more of a sol-gel method, a hydrolysis precipitation method or a gas phase method.

4. The nanocellulose-silicon-based hybrid material according to claim 1, characterized in that: Based on the mass of cellulose, the added amount of silicon dioxide is 1-6 times the mass of cellulose, and the added amount of the silane coupling agent is 0.2-8 times the molar mass of cellulose.

5. A method for preparing the nanocellulose-silicon-based hybrid material according to any one of claims 1 to 4, characterized in that: The silane coupling agent is hydrolyzed to obtain silanol, which is combined with hydroxyl groups on the surface of nano-SiO2 and the surface of nano-cellulose. After drying, the silanol is partially dehydrated to become siloxane wrapped on the surface of nano-cellulose and / or SiO2, and then the nano-cellulose-silicon-based hybrid material powder is obtained by grinding; the process comprises the following steps: (1) Add nano-silicon dioxide powder to a cellulose aqueous suspension at a concentration of 0.05%-0.5%, and disperse it evenly by stirring; (2) Add silane coupling agent and react at 20-85°C with heating and stirring for 10-60 minutes; (3) The reaction solution is dried and then ground to obtain nanocellulose-silicon-based hybrid material powder.

6. An application of the nanocellulose-silicon-based hybrid material according to any one of claims 1 to 4, wherein the nanocellulose-silicon-based hybrid material is used as a filler in a thermoplastic polymer matrix, wherein the thermoplastic polymer matrix comprises: PBAT, PLA, PBS, PP, PE, one or more.

7. The use of the nanocellulose-silicon-based hybrid material according to claim 6, characterized in that: The nanocellulose-silicon-based hybrid material accounts for 0.2-10% of the mass of the polymer matrix, and the particle size of the nanocellulose-silicon-based hybrid material is 30-70 nm.

8. The use of the nanocellulose-silicon-based hybrid material according to claim 6, characterized in that: Adding nanocellulose-silicon-based hybrid materials combining fibers and inorganic particles into thermoplastic polymers can achieve both fiber reinforcement and particle reinforcement. Nanocellulose, as a carrier, improves the dispersibility of inorganic particles, and siloxane encapsulates nanocellulose-silicon-based materials, improving the dispersibility of hybrid materials and compatibility with polymer matrices. The main steps are as follows: (1) blending nanocellulose-silicon-based hybrid materials as fillers with thermoplastic polymer matrices; (2) forming the blended mixture into corresponding products through a thermoforming process; The thermoforming process includes: hot pressing molding, melt temperature 130-170°C, mold temperature 60-80°C, mold pressure 20-50MPa; For extrusion, the temperature of the first feeding section is 100-120°C, the temperature of the second compression section is 120-140°C, the temperature of the third melting section is 140-160°C, the temperature of the fourth homogenizing section is 160-180°C, and the screw speed is 20rpm-200rpm; for injection molding, the barrel temperature is 170-180°C, the mold temperature is 30-70°C, and the injection pressure is 0.3MPa, one or two of the following.

9. A thermoplastic polymer composite material, comprising the nanocellulose-silicon-based hybrid material according to any one of claims 1 to 4 and the thermoplastic polymer matrix according to claim 8, wherein the thermoplastic polymer matrix comprises: PBAT, PLA, PBS, PP, PE, one or more; The nanocellulose-silicon-based hybrid material accounts for 0.2-10% of the mass of the polymer matrix.

Citation Information

Patent Citations

  • In-situ preparation method of cellulose-silicon dioxide composite aerogel

    CN104448397A

  • Microcrystalline cellulose-nanometer silicon dioxide hybrid material and preparing method and application thereof

    CN106519352A

  • Long afterglow luminescent flexible nano cellulose material, preparation method and applications thereof

    CN108059953A

  • Nano silicon dioxide-doped nanocellulose material as well as preparation method and application thereof

    CN110028702A

  • Cis-polybutadiene containing novel environment-friendly filler and preparation method of cis-polybutadiene

    CN110643087A

Cited By

  • Metal coating coated silicon-based material and secondary battery

    CN119419233A

  • Surface sizing agent, preparation method thereof and corrugated board

    CN121087837A